A Textual Analysis of the Chinese Global Talent Management Policy: From a Policy Instruments Perspective - Cai Yueyue; Nor Akmar Nordin; Siti Aisyah Panatik (SAGE Open)
Business will prosper if the environment is conducive to talent gathering. If the environment is nurturing and transformative for workers, it will attract and retain global talent. This study clarifies China’s global talent management policies through a quantitative analysis of the content of global talent management policy texts. We selected two dimensions to explore, namely, policy instrument types and management functions, and constructed a quantitative analysis framework of global talent management policy texts in China. Utilizing the Chinalawinfo Pkulaw Database, which is jointly launched by Peking University and Chinalawinfo Co. Ltd., the keywords “global talent,” “foreign experts,” and “foreign employees” were searched and a total of 145 relevant policy texts were selected. Based on the results, we recommend that for the formulation of future policies of global talent management, the frequency of using policy instruments of customs and traditions should be increased. Additionally, we should promote the integration and cross-cultural adaptation of global talent and strengthen the recognition of foreigners within Chinese culture.